2019
DOI: 10.1039/c9ra03605a
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the efficiency of a bioelectrochemical system: a review

Abstract: The great potential of bioelectrochemical systems (BESs) in pollution control combined with energy recovery has attracted increasing attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(18 citation statements)
references
References 129 publications
0
18
0
Order By: Relevance
“…This suggested that the available nitrogen in the soils was vital for the amount and activity of key bacteria, 27,29 which needs to be further considered. However, EC did not play the supposed role because of few differences in the one‐type soil 50 . For the beta‐diversity, the bacterial community of the cathodic soil or the anodic soil in C was different from that in other treatments, and there was a small difference between OC and Ca, which were obviously different from those in An (Figure S4).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This suggested that the available nitrogen in the soils was vital for the amount and activity of key bacteria, 27,29 which needs to be further considered. However, EC did not play the supposed role because of few differences in the one‐type soil 50 . For the beta‐diversity, the bacterial community of the cathodic soil or the anodic soil in C was different from that in other treatments, and there was a small difference between OC and Ca, which were obviously different from those in An (Figure S4).…”
Section: Resultsmentioning
confidence: 95%
“…However, EC did not play the supposed role because of few differences in the one-type soil. 50 For the beta-diversity, the bacterial community of the cathodic soil or the anodic soil in C was different from that in other treatments, and there was a small difference between OC and Ca, which were obviously different from those in An ( Figure S4). Furthermore, the bacterial communities in the soils near the anode were clearly clustered, as they were in the soils near the cathode ( Figure S5).…”
Section: Relationships Between Bacterial Abundance and Soil Propertiesmentioning
confidence: 90%
“…Jafary et al were able to accomplish desalination of seawater at the rate of 24.3 mg h −1 with the COD removal efficiency of 85% using MDC employing carbon-based electrodes (Jafary et al, 2020). Carbon felt, carbon paper, and graphite electrodes are generally used in MDC, which yielded unsatisfactory performance due to the drawbacks, like low specific surface area, unconducive surface for biofilm formation, low flexibility, and cumbersome maintenance procedures (Pant et al, 2010;Zhang et al, 2019b). Goren and Okten applied a novel 3D carbonaceous electrode for the treatment of geothermal water containing boron and attained 55.5% removal efficiency for boron with simultaneous 91.5% of COD removal in addition to the generation of 9.04 mW m −3 of power density, thus affirming the efficacy of 3D electrodes for application in MDC (Goren and Okten, 2021b).…”
Section: Removal Of Organic Inorganic Compound and Other Suspended And Volatile Mattersmentioning
confidence: 99%
“…or Pseudomonas spp. [9,10,13]. Therefore, it can be assumed that the paddy soil used in this study contained the same species.…”
Section: Characterization Of Anode Surface Morphology and Biofilm Formationmentioning
confidence: 99%
“…On the other hand, microorganisms that exist in the soil play a key role in electricity generation and are affected by the initial soil physicochemical properties such as pH, temperature, moisture content, conductivity, nutrient ions, growth factors, and soil porosity [9].…”
Section: Introductionmentioning
confidence: 99%